Endowing Metal Surfaces With Underwater Superoleophobicity by Femtosecond Laser Processing for Oil-Water Separation Application - Yong, Jiale; Yang, Qing; Hou, Xun; Chen, Feng (Frontiers in Physics, 2020)
In this paper, a widely applicable method that has promise in endowing various metals with oil-water separation ability by femtosecond laser processing is reported. We take an iron sheet as an example to show how to use a femtosecond laser to prepare underwater superoleophobic microstructure on metal substrates and then achieve oil-water separation. An array of through microholes was previously prepared on the iron sheet by a mechanical drilling process. Then, rough nanostructures were created on the surface of the porous sheet by femtosecond laser ablation, resulting in excellent superoleophobicity in water. When the mixture of water and oil was poured onto the porous underwater superoleophobic metal sheet, only the water in the mixture could pass through the sheet while the oil was intercepted, thus the oil/water mixture was successfully separated with high efficiency. Such a novel preparation process and separation manner can extend to different metal substrates. We believe that a wide range of metals like iron sheet can be potentially endowed with oil-water separation ability by femtosecond laser processing because femtosecond laser can process almost all of the metals.